Pengaruh Pemahaman Tujuan Organisasi Terhadap Kinerja Karyawan Mediasi Motivasi Kerja Di Pt Telkom Akses Jakarta Pusat - Heribertus Bao Lile Boro; Fahrul Rizam; Romauli Nainggolan (Jurnal Impresi Indonesia, 2025)
This study examines the influence of understanding organisational goals on employee performance with work motivation as a mediating variable at PT Telkom Akses Central Jakarta. Understanding organisational goals is essential in increasing work motivation and engagement and reducing employee turnover. This research's framework is based on the Goal-Setting Theory, which states that clarity of employees' goals and roles can increase motivation and work productivity. The research approach used is quantitative, using a survey method. Data is collected through a structured questionnaire distributed to 158 employees from various divisions selected using stratified random sampling techniques. The Partial Least Squares (PLS) technique will analyse the relationship between the variables of understanding organisational goals, work motivation, and employee performance. The results of the study indicate that understanding organizational goals has a positive effect on work motivation, work motivation has a positive effect on employee performance, understanding organizational goals has a positive effect on employee performance, and work motivation can positively mediate understanding organizational goals with employee performance at PT Telkom Akses Central Jakarta.